Risk Stratification of Prostate Cancer: Preoperatively Assessing Aggressiveness of Favorable and Unfavorable Intermediate-Risk Groups by Advanced Diffusion-Weighted Imaging - Huang, Hua-Bin; Li, Shu-Yi; Bian, Jie; Luo, Zhong-Xing; Liu, Di-Min; Zhou, Kun-Peng (Journal of Gastrointestinal and Abdominal Radiology, 2025)
The treatment decisions and prognostic outcomes have distinct differences between unfavorable intermediate-risk group (un-FIRG) prostate carcinoma (PCa) and favorable intermediate-risk group (FIRG) PCa. The study aimed to differentiate un-FIRG and FIRG by using advanced diffusion-weighted imaging (DWI).From December 2018 to January 2023, 51 FIRG patients and 67 un-FIRG patients were enrolled in our study. All enrolled PCa patients underwent diffusion kurtosis imaging (DKI) and intravoxel incoherent motion (IVIM) imaging and stretched exponential model using a 3.0-T system. The statistical tests included independent samples t-test and binary logistic regression analysis.Results showed that fractional anisotropy (FA) value and mean kurtosis (MK) value of the un-FIRG (p < 0.001, p < 0.001) were significantly higher than those of the FIRG. On the contrary, mean diffusion (MD), standard apparent diffusion coefficient (ADC), diffusion coefficient (D), and distribute diffusion coefficient (DDC) of the un-FIRG (p = 0.013, p < 0.001, p < 0.001, p < 0.001) were significantly lower than those of the FIRG. Results of binary logistic regression analysis showed that the diagnostic model was statistically significant, chi-square = 90.969, p < 0.001, which could effectively distinguish the 86.40% of un-FIRG in the intermediate-risk group. The results of receiver operating characteristic analysis showed that the area under the curve was 0.9429. Sensitivity and specificity were 88.06 and 84.31%.Compared with the FIRG group PCa, the un-FIRG group PCa exhibits lower standard ADC, D, DDC, and MD values, as well as higher FA and MK values. This suggests that preoperative advanced DWI may serve as an imaging biomarker for distinguishing between the FIRG group and un-FIRG group PCa.Combining preoperative advanced DWI (DKI, IVIM imaging, and the stretched exponential model) shows potential for noninvasive subrisk stratification of intermediate-risk group PCa.
Keywords: prostate cancer; intermediate-risk group; diffusion kurtosis imaging; intravoxel incoherent motion imaging; stretched exponential model